(untitled) (Proceedings of the International Conference on Public Health, 2019)
Antenatal care (ANC) is a major component of maternal health services for preventing adverse pregnancy outcomes. As one of maternal health indicator for universal health coverage and Sustainable Development Goals (SDGs), it is important to monitor the distribution of the coverage among social dimension stratification. The study aims to examine inequality trends in the use of ANC services of Indonesian women aged 15-49 years based on the data from the Indonesia Demographic Health Surveys (IDHS) 2002, 2007 and 2012. Inequalities are measured using socioeconomic and demographic stratification variables such as urban-rural, mother’s education and household wealth index. We also performed analysis of social determinants of health and their relationship with ANC. The trend of ANC utilization shows narrower gap according to social dimension stratification. The urban-rural difference for ANC has been reduced from 15 to 10.5 percentage points. The education-related inequality in ANC also declined nearly 40% from 2002 to 2012. A similar downward trend was observed for wealth-related inequality merely between the last two periods of survey. The trend in ANC use was entirely confounded by socioeconomic and demographic changes over time. The adjusted odds ratios for wealth quintile and education substantially decreased. A reduction in the inequality dimension through time suggests that both access and equality are improving in ANC use. Monitoring of trends needs to be continuously done among disadvantaged groups so that programs are in place for more targeted health development plans.